Contraction Dynamics and Respiration of Small Single-Osculum Explants of the Demosponge Halichondria panicea - Kumala, Lars; Canfield, Donald Eugene (Frontiers in Marine Science, 2018)
: Sponges pump large amounts of seawater through their water canal system, providing both food and oxygen to the sponge body. Sponge pumping activity may show considerable variation as a consequence of contractile behavior, which includes contraction and expansion of the exhalant opening (osculum) in regular or irregular time intervals. The present study unravels short- and long-term effects of contraction-expansion events on the respiration rate of small single-osculum explants of the demosponge Halichondria panicea. Based on simultaneous video-microscopic time-lapse recordings of osculum cross-sectional area (OSA) and projected area (A), combined with respiration rate measurements, we further evaluate the role of pumping activity for oxygen uptake in the explants. Pumping dynamics were expressed by cyclic contraction-expansion events of the OSA and A, including osculum closure with a mean duration of 37.5 ± CI95% 13.7 min. The respiration rate of sponge explants remained relatively constant at 0.046 ± CI95% 0.014 µmol O2 h-1 (i.e., 7.41 µmol O2 h-1 g-1 DWsponge) during contraction-expansion cycles, but with a marginal decrease of 9.6 % during osculum closure. Periods of pumping cessation during osculum closure likely caused reduced oxygen levels in the sponge body, increasing the oxygen gradient between the environment and the sponge interior, allowing enhanced diffusion of oxygen across the explant surface. This is a key mechanism for balancing respiratory demands during sponge contractions. While contractile behavior is only marginally associated with decreased respiratory demands in small single-osculum H. panicea explants, it may control the degree of internal oxygen depletion and thereby ensure maintenance of sponge-associated microorganisms during non-pumping periods.